Peran Kelompok HKm Wanamina Dalam Inovasi Alternatif Ekonomi Masyarakat Desa Kota Kapur - Madun Mustofa; Fitri Ramdhani Harahap; Laila Hayati (CV. Multi Kreasi Media, 2023)
This study examines the role of the Wanamina HKm Group in the economic alternative innovation of the Kota Kapur Village Community. Innovation is a way to answer problems faced by community groups. Innovations applied in the empowerment activities of the Wanamina HKm Group to manage its natural and human resources in order to provide the ability to increase income as an economic alternative for the local community while providing greening to the environment of mangrove forest areas. The theory used in this study is the diffusion theory of innovation from Everett M. Rogers and F. Floyd Shoemaker with the method used in this study is a descriptive qualitative method. The number of informants in this study was 14 people. The data collection techniques used are interviews, observations and documentation. The data sources in this study are from primary data and secondary data. This research was analyzed through 3 stages including data reduction, data display, and drawing conclusions. The results of the research obtained from the field, that the economic condition of the people of Kota Kapur Village has decreased due to several things including damaged fishing gear for fishermen, the selling price of tin has decreased, and the Covid-19 Pandemic. This condition gave rise to the empowerment program of the Wanamina HKm group with reforestation activities, shellfish and honey cultivation, marine tourism as an economic alternative for the people of Kota Kapur Village. The impacts caused by these activities include, strengthening solidarity, the condition of forests and beaches becoming maintained, government assistance to fishermen is more targeted, new businesses emerge from the cultivation of shellfish and honey such as nurses of cultivation sites.